Oil removal from water by filtration - Mažeikienė, Aušra; Rimeika, Mindaugas; Švedienė, Sigita (Journal of Environmental Engineering and Landscape Management, 2014)
Oil-contaminated water is most commonly treated with sorbent materials. In this experimental study, a fibrous sorbent material Fibroil was used. The experiment was carried out with tap water and clarified stormwater. It was determined that the retention of contaminants is worse at high fow rates, which reduces the efficiency of treatment. Sorbent materials retain suspended solids and reduce water turbidity; thus, the water must be clarified and pretreated before it is supplied to the sorption fillings. For the efficient use of sorbent material properties, the concentration of suspended solids in water supplied to the filter must be below 20 mg/L, while water turbidity must be below 15 NTU and the flow rate must be below 20 m/h. If the pressure loss in the sorption filler increases to 25 cm, it can be predicted that the oil concentration after treatment would exceed permissible environmental requirements (5 mg/L). The derived sorption and hydraulic properties of the material can be used to evaluate the efficiency of existing operative stormwater treatment plants as well as to design new facilities.